Atmospheric temperature changes over the 20th century at very high elevations in the European Alps from englacial temperatures. Issue 10 (23rd May 2013) - Gilbert, A.; Vincent, C.
Abstract [1] Given the paucity of observations, a great deal of uncertainty remains concerning temperature changes at very high altitudes over the last century. Englacial temperature measurements performed in boreholes provide a very good indicator of atmospheric temperatures for very high elevations although they are not directly related to air temperatures. Temperature profiles from seven deep boreholes drilled at three different sites between 4240 and 4300 m above sea level in the Mont Blanc area (French Alps) have been analyzed using a heat flow model and a Bayesian inverse modeling approach. Atmospheric temperature changes over the last century were estimated by simultaneous inversion of these temperature profiles. A mean warming rate of 0.14°C/decade between 1900 and 2004 was found. This is similar to the observed regional low altitude trend in the northwestern Alps, suggesting that air temperature trends are not altitude dependent.